Pengaruh Lingkungan Keluarga terhadap Keputusan Bersekolah melalui Persepsi Siswa Muslim Sebagai Variabel Intervening di SMP Santo Yoseph Denpasar-Bali - Jumari; Rusma; Nikita Rachmawati Pabela (At Turots: Jurnal Pendidikan Islam, 2025)
Ideally, Muslim students choose schools that can support academic development while simultaneously shaping religious character in accordance with Islamic values. However, over the past five years, an interesting phenomenon has occurred at Santo Yoseph Junior High School in Denpasar, a private Catholic-based school: a significant increase in the number of Muslim students enrolling and attending. This phenomenon indicates a shift in educational preferences that is no longer entirely based on formal religiosity aspects but also involves other considerations, such as the family environment and students' perceptions of the school. This study aims to analyze descriptive statistics and test the structural model of family environment, Muslim students' perceptions, and schooling decisions, as well as to test and explain the direct and indirect influence of the family environment on schooling decisions through the perception of Muslim students as an intervening variable. The research method used is quantitative ex post facto, conducted on all Muslim students at Santo Yoseph Junior High School Denpasar. The data collection instrument used was a questionnaire. Data analysis was performed using the SEM-PLS test. The results show that: 1) Descriptively, the variables of family environment, Muslim students' perception, and schooling decision are in the good/high category; 2) The structural model is empirically proven and has good predictive relevance with a Q² value > 0 at a ρ value of 0.000; 3) There is a positive and significant direct influence of the family environment on Muslim students' perception; 4) There is a positive and significant direct influence of Muslim students' perception on the schooling decision; 5) There is a positive and significant direct influence of the family environment on the schooling decision; 6) There is a positive and significant indirect influence of the family environment on the schooling decision at Santo Yoseph Junior High School Denpasar through Muslim students' perception.